Peran Mr. Frederik Lodewijk Anthing dalam Pekabaran Injil Di Pinggir Batavia (1870 – 1883) - Jeremy Christian Karamoy; Humaidi Humaidi; Nurzengky Ibrahim (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This article discusses the role and contributions of Mr. Frederik Lodewijk Anthing in the process of evangelism in the outskirts of Batavia in the 19th century, particularly in relation to the inception of the Pasundan Christian Church. Without a background in formal theological education, Anthing demonstrated a high missionary spirit and an innovative contextual approach. He not only evangelized directly but also empowered and educated indigenous youth as local evangelists with a delivery style that suited the culture and mindset of the local community. This research employs historical methods through stages of heuristics, source criticism, interpretation, and historiography to trace and analyze mission strategies, cultural challenges, and the long-term impacts of Anthing's ministry. The research results show that Anthing has laid an important foundation for indigenous Christianity in West Java, despite facing various criticisms from colonial missionary institutions regarding his approach, which was deemed not to meet formal standards. Nevertheless, Anthing's thoughts and strategies in preaching the Gospel through indigenous people and in indigenous ways have made him an original and visionary figure in the history of evangelism in Indonesia.